Effects of neutral and enthusiastic praise on the rate of discrimination acquisition. Issue 2 (14th February 2018) - Weyman, Jennifer R.; Sy, Jolene R.
Abstract : Previous research has shown that praise is an effective reinforcer; however, few researchers have evaluated whether qualitative differences in praise affect responding. The purpose of the current study was to compare the effects of neutral, enthusiastic, and no praise on the rate of matching‐to‐sample acquisition during discrete‐trial training with adults diagnosed with autism and an intellectual disability. In addition, we evaluated preference for neutral, enthusiastic, and no praise. All three participants acquired responses slightly faster during the enthusiastic praise condition. Preference assessment results showed that one participant preferred enthusiastic praise, whereas the two other participants showed indiscriminate selections.